The Role of Bank Profitability and Liquidity in Indonesia's Economic Growth: An Empirical Study on ROA, LDR, and CAR - Rahmatullah, Dedy; Kartini (Universitas Indo Global Mandiri, 2025)
This study analyzes the role of banking profitability and liquidity in influencing Indonesia’s economic growth within a context of heightened macroeconomic volatility. While previous research has examined bank credit, assets, or profitability individually, empirical evidence remains limited regarding the simultaneous interaction between profitability and liquidity and their transmission to economic growth, particularly when external pressures such as inflation and exchange rate fluctuations are taken into account. This gap is critical for bank-based economies like Indonesia, where disturbances in liquidity and profitability rapidly affect intermediation capacity and real-sector performance. To address this gap, the study employs monthly data from 2018 to 2024 and applies a Vector Error Correction Model (VECM), complemented by Impulse Response Functions (IRF) and Forecast Error Variance Decomposition (FEVD). Banking performance is measured using Return on Assets (ROA), Loan to Deposit Ratio (LDR), and Capital Adequacy Ratio (CAR), while inflation and exchange rate serve as macroeconomic control variables. The results show that ROA, LDR, CAR, inflation, and the exchange rate significantly affect economic growth in both the short and long run, with profitability and liquidity variables exerting relatively stronger influences than macroeconomic factors. These findings provide evidence on how internal banking conditions interact with external shocks in shaping economic dynamics. The study offers implications for the design of macroprudential policies and contributes to the literature by integrating profitability and liquidity indicators within a unified empirical framework that accounts for macroeconomic instability Keywords: Economic Growth, Banking Sector, LDR, ROA, CAR, VECM, FEDV, Indonesia